Penerapan Kode Etik Dan Etika Profesi Akuntan Publik - Regita Cahyani Agustina; Patricia Amanda; Fiska Apriyanti Jumadi; Chasimiriona Frima Kidak; Nabila Nursyahbania Zachra (PT. Saha Kreasi Indonesia, 2025)
The public accounting profession plays a strategic role in maintaining transparency, accountability, and the reliability of financial information used as a basis for business and public decision-making. To maintain public trust, public accountants are required to adhere to the codes of ethics and professional conduct established by professional organizations such as the Indonesian Institute of Accountants (IAI) and the Indonesian Institute of Public Accountants (IAPI). However, the implementation of these codes of ethics still faces challenges, as evidenced by numerous cases of accounting ethics violations in Indonesia. This study aims to analyze the application of the codes of ethics and professional conduct of public accountants. This study employed a library research method, examining theories and various scientific reference sources relevant to the research topic. The approach used was descriptive qualitative. Data collection techniques were conducted through reviewing written sources such as books, journals, articles, and previous research reports. Data analysis was conducted using content analysis to obtain valid conclusions by selecting, grouping, and comparing information according to the research focus. The research findings indicate that the application of the public accountant code of ethics, which encompasses the principles of integrity, objectivity, professional competence and due care, confidentiality, and professional conduct, plays a crucial role in maintaining the quality of service and the credibility of the accounting profession. Therefore, it is concluded that the application of the public accountant code of ethics can maintain the dignity of the profession, protect public interests, and increase trust in the financial reports and information they produce.